Petunia Performance Under Application of Animal-Based Protein Hydrolysates: Effects on Visual Quality, Biomass, Nutrient Content, Root Morphology, and Gas Exchange - Cristiano, Giuseppe; De Lucia, Barbara (Frontiers in Plant Science, 2021)
Sustainable plant production practices have been implemented to reduce the use of synthetic fertilizers and other agrochemicals. One way to reduce fertilizer use without negatively impacting plant nutrition is to enhance crop uptake of nutrients with biostimulants. The aim of this research was to evaluate the effect of a commercial animal-based protein hydrolysate (PH) biostimulant on the visual quality, biomass, macronutrient content, root morphology and leaf gas exchange of a petunia (Petunia x hybrida Hort. 'Red') under pre-harvest conditions. Two treatments were compared: a) three doses of an animal-based PH biostimulant: 0 (D0 control), 0.1 (D0.1 - normal), and 0.2 gL−1 (D0.2 - high); b) two biostimulant application methods: foliar spray and root drenching. The Dose x Method interaction effect of PH biostimulant on the plants was significant in terms of quality grade and fresh and dry biomass. The high dose applied as foliar spray produced petunias with Extra grade visual quality (number of flowers per plant 161, number of leaves per plant 450 and leaf area per plant 1487 cm2) and a total above-ground dry weight of 35 g, shoots (+91%), flowers (+230%) and leaf fresh weight (+71%). P and K content were higher than in untreated petunias, when plants were grown with D0.2 and foliar spray. With foliar spray at the two doses, SPAD showed a linear increase (+21.6% and +41.0%) with respect to untreated plants. The Dose x Method interaction effect of biostimulant application was significant for root length, projected and total root surface area, number of root tips, forks and crossings. Concerning leaf gas exchange parameters, applying the biostimulant at both doses as foliar spray resulted in a significant improvement in net photosynthesis (D0.1: 22.9 µmol CO2 m-2 s-1, D0.2: 22.4 µmol CO2 m-2 s-1) and stomatal conductance (D0.1: 0.42 mmol H2O m-2 s-1 and D0.2: 0.39 mmol H2O m-2 s-1) compared to control. These results indicate that application of PH biostimulant at 0.2 gL-1 as foliar spray helped to achieve Extra grade plants, and that this practice can be exploited in sustainable greenhouse conditions for commercial production of petunia.